(3Gdcga hGdQbje aj TQM HSe Gddg GdQMef GdQMjes - (3YHO GdcQje Hf EHQGgje Hf YHO GdcQje GdLjdj GdUhaj , bWH GdOjf,J (B832 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdcGef ai cfg PGJg CeG HYO Gfg bO hQO ai GdNHQ Yfg Udi Gddg Ydjg hSde Cfgb Gd ai GdcJH GdefRdI agh ai GdbQBf GdMOjK s
(3BNQgG (B:s
(3hdG cGf eG bdJe hdG cGf eG bdfG hdG jfJe YfG hdG Yfce HfG GfJgJ GdQSGdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B313s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(1 / 2727) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs